Control of nonlinear two-tank hybrid system using sliding mode controller with fractional-order PI-D sliding surface. (October 2018) - E., Govinda Kumar; J., Arunshankar
Abstract: In this work, a sliding mode controller (SMC) with a fractional-order proportional plus integral plus derivative (FOPID) sliding surface for level control in a two-tank hybrid system is developed. A modified SMC with a fractional-order PI-D (FOPI-D) sliding surface is also proposed, in which the output of the system is directly applied to the derivative term of the sliding surface equation. The performance of the proposed controller is found to improve with an increase in the fractional value of the derivative term in the FOPI-D sliding surface. The performances of the two controller designs are compared with that of an SMC with a fractional-order PD (FOPD) sliding surface, taken from the literature. A simulation study, carried out with set points above and below a threshold value, revealed that the proposed SMC with the FOPI-D sliding surface delivers better closed-loop performance than conventional SMC, SMC with FOPD and SMC with FOPID sliding surfaces.